Impact and mechanism analysis of bank agglomeration on high-growth enterprise carbon intensity: evidence from China - Xu, Ling; Lu, Danning; Shi, Jianxun (Frontiers in Environmental Science, 2024)
Financial agglomeration contributes to energy efficiency improvement and carbon emission reduction, but more micro-level evidence is needed to further support it. Based on the data of high-growth enterprises and bank branches in China, this study examines the impact of bank agglomeration on carbon intensity of high-growth enterprises. The results suggest that bank agglomeration facilitates the reduction of carbon intensity in high-growth enterprises. Specifically, bank agglomeration significantly reduces carbon intensity in non-state-owned enterprises, while it has no significant effect on state-owned enterprises. Compared with state-owned commercial banks and small banks, the agglomeration of joint-stock commercial banks has the strongest promoting effect on enterprise carbon reduction. Bank agglomeration has a particularly significant effect on the carbon reduction of enterprises in high-energy-consuming industries and high-polluting industries. Mechanism analysis shows that bank agglomeration reduces enterprise carbon intensity by promoting innovation, changing energy structure, and mitigating financial constraint. These findings carry important policy implications, suggesting that policymakers should leverage financial agglomeration as a tool for carbon reduction and sustainable development.